PERBANDINGAN PENGATURAN TINDAK PIDANA HOMOSEKSUAL MENURUT HUKUM PIDANA INDONESIA DAN HUKUM PIDANA ISLAM DI BEBERAPA NEGARA DENGAN MAYORITAS PENDUDUK BERAGAMA ISLAM - Rima Rohmiati; Erdianto Erdianto; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the problems that insult the Indonesian nation today is Homosexual crime. Homosexuality asa sexual orientation of the same sex, which deviates greatly from the norms, religion, law, Pancasila, moralsand customs of Indonesian citizens. Homosexual behavior often leads to the mental and psychologicalhealth of the victims. In Islam it also strictly prohibits homosexual acts, the consequences for health andpsychology are very serious. Often cases of Homosexual crimes appear and come to light after a number ofvictims report them. The effects of homosexual crime lead to mental trauma, injury to the genitals andrectum and potential future perpetrators for both boys and men. Not only the State of Indonesia, countrieswith very strict Muslim populations prohibit homosexual acts in their countries, so that homosexuality isdefined as a criminal offense in these countries.This type of research is normative legal research, namely using literature study to search the data.This research is descriptive in nature which tries to provide data as thorough and as detailed as the existingproblems. In this study using qualitative data analysis which means explaining and concluding about thedata collected by the author. This research uses secondary data or codified scientific data.The results of this study are to explain that the prohibition for homosexual perpetrators is clearlyregulated in the Al-Qur'an and Hadith. As well as in the Indonesian National Law has been regulated, but itis lacking in categories and the need for additional stops for Homosexual offenders. This regulatesregulations regarding Homosexuals in Indonesia which are not yet perfect. The author provides an idealconcept of rehabilitation for Homosexual offenders and differentiates between Homosexual offenders andnon-Homosexual sex offenders, and adds a category for Homosexual crime victims. So it is hoped that thepre-ban can minimize Homosexual crimes in the future.Keywords: Homosexual - Indonesian Criminal Law - Islamic Criminal Law